How do you solve -7( x + 3) = - 63?

2 Answers
May 8, 2018

=>x = 6

Explanation:

We start with

-7(x+3) = -63

We distribute the LHS

-7x-21 = -63

We add 21 to both sides

-7x = -42

We divide both sides by -7

=>x = 6

May 8, 2018

The answer to the problem is color(red)(x=6).

Explanation:

Start by distributing -7 to (x+3).

-7x-21=-63

Add 21 to both sides.

-7x=-42

And finally, divide both sides by -7.

(-7x)/-7=(-42)/-7

x=6

Plug it back in to check your answer:

-7(x+3)=-63
-7(6+3)=-63
-7(9)=-63
-63=-63

Which proves that the answer is x=6.